The given expression can be simplified to: 3b-a
a + b + c = 180 b = 3a c = 5a Substituting the values of b and c into the first equation. a + 3a + 5a = 180 or 9a = 180 so that a = 20 then b = 3a = 3*20 = 60 and c = 5a = 5*20 = 100
3 a b =3a b
The idea here is to combine terms that have the same variable (or, in more complicated cases, the same combination of variables). For example, 3a + 2a is the same as 5a.
What is the solution of -2a plus 3a plus 5b
p=b+3a+c p-3a-c=b+3a-3a+c-c p-3a-c=b b=p-3a-c
If a + b = 6, what is the value of 3a + 3b?
This expression can be factored. ab + 3a + b2 + 3b = a(b + 3) + b(b + 3) = (a + b)(b + 3)
3a+ax+3b+bx = 3(a+b)+(a+b)x = (a+b)(3+x)
It is simply as stated in the question. Without information about a or b, the expression cannot be simplified nor evaluated.
= a + b - 2
3ab + 3ac + 2b2 + 2bc = 3a(b + c) + 2b(b + c) = (3a + 2b)(b + c)
-2a plus 3b
Thenx = (c - b) / 3a